2016
DOI: 10.1007/s10753-016-0448-6
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Epoxide Hydrolase Inhibitor Suppresses the Expression of Triggering Receptor Expressed on Myeloid Cells-1 by Inhibiting NF-kB Activation in Murine Macrophage

Abstract: Triggering receptors expressed on myeloid cell-1 (TREM-1) is a superimmunoglobulin receptor expressed on myeloid cells. TREM-1 amplifies the inflammatory response. Epoxyeicosatrienoic acids (EETs), the metabolites of arachidonic acid derived from the cytochrome P450 enzyme, have anti-inflammatory properties. However, the effects of EETs on TREM-1 expression under inflammatory stimulation remain unclear. Therefore, inhibition of soluble epoxide hydrolase (sEH) with a highly selective inhibitor [1-trifluorometho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…Depletion or blocking TREM-1 has shown protective effects in sepsis, ischemia-reperfusion, pancreatitis, inflammatory bowel diseases, Fungal Keratitis and arthritis14151617181920. Our previous study found that the expression of TREM-1 in LPS-induced ALI mice lung and macrophages are significantly increased, suggesting an important role of TREM-1 in ALI2122. Although the pro-inflammatory effect of TREM-1 and its implication in the pathogenesis of inflammatory diseases are emerging, the mechanisms are still poorly understood.…”
mentioning
confidence: 97%
“…Depletion or blocking TREM-1 has shown protective effects in sepsis, ischemia-reperfusion, pancreatitis, inflammatory bowel diseases, Fungal Keratitis and arthritis14151617181920. Our previous study found that the expression of TREM-1 in LPS-induced ALI mice lung and macrophages are significantly increased, suggesting an important role of TREM-1 in ALI2122. Although the pro-inflammatory effect of TREM-1 and its implication in the pathogenesis of inflammatory diseases are emerging, the mechanisms are still poorly understood.…”
mentioning
confidence: 97%
“…DAP12 is a transmembrane protein with an immunoreceptor tyrosine-based activation motif (ITAM) signaling unit [33]. TREM-1 consists of an extracellular domain, a transmembrane region, and a short cytoplasmic domain which lacks any signaling motifs [32].…”
Section: Triggering Receptor Expressed On Myeloid Cells (Trem)-1mentioning
confidence: 99%
“…The overarching goal of this research should be finding a way to use TREM receptors as interventional methods to reverse or arrest progression for periodontal diseases and systemic infections. There are several studied methods of TREM-1 manipulation, all of which could provide novel treatment methodologies for periodontal disease [17,21,27,33,53]. Synthetic TREM-1 blockade could mitigate the host inflammatory response and be useful as an adjunct therapy for the treatment of periodontal disease.…”
Section: Five-year Viewmentioning
confidence: 99%
“…The implication of hydrolase activity of sEH in the metabolism of epoxyeicosatrienoic acids (EETs), inflammation and hypertension has been well documented . For example, pharmacological inhibition of the EH activity of sEH or deletion of the sEH gene causes an increase in the accumulation of EETs and leads to the attenuation of angiotensin II–induced hypertension and cardiac hypertrophy and lipopolysaccharide‐induced inflammation in vitro and in vivo . Oral administration with inhibitors targeting EH activity of sEH or genetic disruption of sEH significantly retards the progression of atherosclerosis in hyperlipidemic mouse models .…”
Section: Introductionmentioning
confidence: 99%
“…causes an increase in the accumulation of EETs and leads to the attenuation of angiotensin II-induced hypertension and cardiac hypertrophy and lipopolysaccharide-induced inflammation in vitro and in vivo. [5][6][7][8] Oral administration with inhibitors targeting EH activity of sEH or genetic disruption of sEH significantly retards the progression of atherosclerosis in hyperlipidemic mouse models. 9,10 Multiple lines of evidence demonstrate that the PT domain of sEH also has a crucial role in the regulation of cholesterol metabolism and cell growth in hepatocytes.…”
mentioning
confidence: 99%